Cultural journalists on social media - Kristensen, Nete Nørgaard; From, Unni (MedieKultur: Journal of media and communication research, 2018)
This article investigates the use of social media among a particular group of journalists: cultural journalists. Combining research on social media journalism with research on cultural journalism and applying a mix-method approach, the study shows that use of social media is still a fairly random practice in cultural newsrooms. It also shows that cultural journalists use their Twitter and Facebook accounts interchangeably as tools for professional communication in their daily work and for personal communication in their daily lives. In other words, their social media practices blur the boundaries between institutional interests and professional identities, and more private interests and personal identities. While this may be a challenge to most journalists, it resonates well with the professional logics of cultural journalists. They have long practiced their work in a grey-zone between the public and the private, and the objective and subjective. Through their social media practices, they promote the media institution they work for and their own ‘personalised’ professional brand.